2011
DOI: 10.3736/jcim20111108
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture combined with Chinese herbal medicine Plantain and Senna Granule in treatment of functional constipation: a randomized, controlled trial

Abstract: Acupuncture plus Plantain and Senna Granule can significantly decrease gastrointestinal transit time and defecation cycle in patients with functional constipation; it can also change stool property and alleviate constipation symptom and accompanying symptoms, with good security and tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…The control groups in the literature included medications, other methods of stimulation, and acupuncture plus medications. Medications used in the control group included conventional medicine [ 15 , 16 , 23 , 24 ] (Mosapride, Macrogol 4000, Lactulose) and Chinese herbal medicine [ 15 , 22 ] (Fuzhengliqi mixture and Plantain and Senna Granule). Sham acupuncture [ 17 , 27 , 29 ], shallow acupuncture [ 16 , 23 , 24 ], regular electrical stimulation [ 19 ], and other methods of stimulation were performed as control methods.…”
Section: Acupuncturementioning
confidence: 99%
See 2 more Smart Citations
“…The control groups in the literature included medications, other methods of stimulation, and acupuncture plus medications. Medications used in the control group included conventional medicine [ 15 , 16 , 23 , 24 ] (Mosapride, Macrogol 4000, Lactulose) and Chinese herbal medicine [ 15 , 22 ] (Fuzhengliqi mixture and Plantain and Senna Granule). Sham acupuncture [ 17 , 27 , 29 ], shallow acupuncture [ 16 , 23 , 24 ], regular electrical stimulation [ 19 ], and other methods of stimulation were performed as control methods.…”
Section: Acupuncturementioning
confidence: 99%
“…Sham acupuncture [ 17 , 27 , 29 ], shallow acupuncture [ 16 , 23 , 24 ], regular electrical stimulation [ 19 ], and other methods of stimulation were performed as control methods. Combinational use of medications included EA plus Fuzhengliqi mixture [ 15 ], and EA plus Plantain and Senna Granule [ 22 ]. There was only one trial in which two kinds of stimulation methods, acupuncture and moxibustion, were used together [ 21 ].…”
Section: Acupuncturementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies[2526272829303132333435] concerning the location of acupoints in acupuncture treatment for primary depression showed that the main points are located in Du meridian, pericardium meridian, spleen meridian, liver meridian and stomach meridian; the common points are Baihui (DU20) and Yintang (EX-HN3). First, Du meridian[36] is responsible for regulating consciousness disease and organ lesions. Baihui [25] belongs to Du meridian and regulates mentality.…”
Section: Discussionmentioning
confidence: 99%
“…They have also been shown to have analgesic effects in rats subjected to chronic visceral hypersensitivity [61, 62]. They regulate gastrointestinal function in human patients [63, 64]. In the present study, the intensity of infrared radiation of bilateral ST25 and the control points in UC rats were measured using a hypersensitivity PHE201 infrared spectrum analyzer [1, 22].…”
Section: Discussionmentioning
confidence: 99%